Electron-Transfer Reduction of Butyryloxymethyloxirane with Alkalide K-, K+ (15-Crown-5)2 - Grobelny, Zbigniew; Stolarzewicz, Andrzej; Szczepanski, Marcin; Maercker, Adalbert (Letters in Organic Chemistry, 2006)
Butyryloxymethyloxirane (glycidyl butyrate) is efficiently reduced with potassium anions of alkalide K-, K+(15-crown-5)2. The reaction proceeds via the corresponding radical anion, which decomposes the homolytic alkyl-oxygen bond cleavage or dimerizes. The oxirane ring is not opened by K-. No organometallic is formed as an intermediate. This shows that the mechanism of the process under study differs from that proposed earlier for alkyl glycidates. The position of the ester group in the substituent influences the behavior of the oxiranes.
Keywords: potassium anion